Native language resources can illuminate global darkspots in utilized plant species and reduce data shortfalls - Tuan Nguyen; Tuan Nguyen; Ana Sofía Monroy-Sais; Gabriela Rabeschini; Gabriela Rabeschini; Esra Per; Mohammed Abdul Kareem (Frontiers in Sustainable Food Systems)
The 2022 IPBES Sustainable Use of Wild Species Assessment states that humans collectively utilize about 31,100 plant species globally, roughly 7 percent of all described plant species. This is a conservative estimate acknowledged in the Assessment but is not clearly mentioned in the Summary for Policymakers report. This number is drawn from the Kew's State of the World's Plants and Fungi Reports, where the knowledge gap of species used and valued by humans in many regions (plant darkspots) is acknowledged. This article discusses this gap and its perpetuation while highlighting that Indigenous, Local, and Traditional Ecological Knowledge can remediate such global biodiversity data shortfalls. We propose that oral and written native language resources could enhance understanding and data coverage of species use, especially in biodiversity darkspots. To support this, we examine how native language resources have supported the documentation of species use in five countries—India, Brazil, Türkiye, Mexico, and Vietnam. Finally, we discuss barriers and opportunities, and call for policymakers, data managers, and other beneficiaries to systematically include native language resource insights, starting from the local and national levels and moving toward global aggregation.